KONTRIBUSI USAHATANI KELAPA SAWIT DALAM MENINGKATKAN KESEJAHTERAAN RUMAHTANGGA PETANI DI KABUPATEN ACEH UTARA - Jamilah Jamilah; Mawardati Mawardati; Ghazali Syamni (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Oil palm as a leading export commodity in Aceh Province in its development faces obstacles both at the cultivation and post-harvest and marketing levels which will determine the income and welfare of farmers. This study aims to analyze the contribution of oil palm farming in improving farmer welfare. The research method used a survey method of smallholder oil palm farmers. The results showed that oil palm farming was categorized as contributing enough to improving the welfare of farmer households. To achieve a decent living category, farmers must own 2.08 hectares of land or a minimum selling price of Rp1,553.40 per kg. Increasing productivity of oil palm should be a priority scale in anticipating fluctuations in CPO prices which have implications for fluctuations in the selling price of TBS at the farm level.